CFD Investigation of the effects of bubble aerator layouts on hydrodynamics of an activated sludge channel reactor. Issue 20 (6th September 2019) - Hreiz, Rainier; Potier, Olivier; Wicks, Jim; Commenge, Jean-Marc
ABSTRACT: In this paper, computational fluid dynamics (CFD) simulations are employed to characterize the effects of bubble aerator layouts (i.e. spatial arrangement) on the hydrodynamics in activated sludge (AS) reactors. The first configuration considered is a channel reactor with aerators placed alongside one lateral wall, for which velocity measurements are available in literature. CFD results were in good agreement with experimental data, which proves that the model is sufficiently accurate and predictive. Accordingly, simulations and numerical residence time distribution tests were conducted for different aerator layouts to determine their effects on the reactor hydrodynamics. The results revealed that the flow characteristics are extremely sensitive to the aerators arrangement given the high gas flow rates used in AS processes. Among the layouts investigated, the one where diffusers are placed all over the reactor floor has led to the least dispersive flow, i.e. which characteristics best tend toward that of an ideal plug flow reactor. Indeed, this flow field presented the lowest average turbulent diffusion and the most uniform axial velocity and turbulence fields. Such a flow behaviour is expected to be highly beneficial for biological treatment since it reduces pollutant dilution by axial diffusion and limits raw wastewater channelling to the outlet.